Severe Irritant Contact Dermatitis Causing Skin Ulceration Secondary to a Testosterone Patch - Nathan Lawrentschuk; Neil Fleshner (The Scientific World Journal)
Testosterone replacement has undergone somewhat of a revolution in the past decade with the introduction of topical administration techniques, including patches and gels, as well as an increasing interest in the treatment of older men with low testosterone levels for what is now termed andropause. Increasingly, testosterone replacement therapy is being individually tailored. Side effects to skin patches have been reported with irritant contact dermatitis being the most common. However, ulceration has previously not been reported. Herein, we present a case that highlights testosterone transdermal therapies, their potential side effects and management strategies, and broadens our knowledge as we approach an era where these types of treatments are likely to be more common.